Development of a highly efficient protoplast regeneration and transfection protocol for enhancing CRISPR genome editing of Brassica carinata - Li, Xueyuan; Tesfaye, Misteru; Sandgrind, Sjur; Guan, Rui; Zhu, Li-Hua (Frontiers in Plant Science, 2025)
Brassica carinata is an important oil crop with significant potential for food and industrial production. The application of the CRISPR/Cas9 genome editing tool in B. carinata could accelerate its breeding cycle. However, no efficient DNA-free gene editing method currently exists for this species. Protoplast-based CRISPR editing presents a promising solution, though it is often challenging for many crop species. In this study, we investigated several critical factors influencing in vitro shoot regeneration, including genotype, sugar type, selection and combination of plant growth regulators (PGRs), and culture duration on different media throughout various stages of protoplast development. As a result, we developed a highly efficient, five-stage protoplast regeneration protocol for B. carinata based on specific stages of protoplast development. Key findings of this study include the requirement for high concentrations of NAA and 2,4-D in the initial medium (MI) for cell wall formation, while a lower auxin concentration relative to cytokinin was necessary for active cell division (MII). For callus growth and shoot induction, a high cytokinin-to-auxin ratio was essential (MIII), and an even higher cytokinin-to-auxin ratio was optimal for shoot regeneration (MIV). For shoot elongation, low levels of BAP and GA3 were sufficient (MV). Our results also demonstrated that the duration of culture on different media and maintaining appropriate osmotic pressure at the early stages were crucial for successful protoplast regeneration. With this optimized protocol, we achieved an average regeneration frequency of up to 64% and a transfection efficiency of 40% using the GFP marker gene. This efficient protoplast regeneration protocol is now being employed for genome editing in our lab and is expected to significantly enhance the application of the CRISPR system in both basic research and the genetic improvement of B. carinata over the long term.